2021
DOI: 10.1111/ane.13564
|View full text |Cite
|
Sign up to set email alerts
|

The CHA2DS2‐VASc risk score predicts successful endovascular treatment in patients with acute ischemic stroke

Abstract: Objectives Acute ischemic stroke is a common cause of mortality and morbidity worldwide. Percutaneous endovascular intervention is an important treatment method in ischemic stroke. Endovascular procedure success is associated with the clinical outcome of the patients. The CHA2DS2‐VASC score is an important score used to determine the risk of ischemic stroke in patients with atrial fibrillation. In our study, we aimed to evaluate the relationship between procedure success and CHA2DS2‐VASC score in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…As a result of this study, the CHA2DS2-VASc score was found to be significantly higher in the patient group with mTICI flow < 2c (2.78 ±1.44, 5.02 ±1.77, p < 0.001). In addition, a CHA2DS2-VASc score ≥ 3 was determined as a predictor of a failed attempt (area under the curve (AUC) = 0.827, 95% CI: 0.739–0.895, p < 0.001) [ 17 ]. Similarly, in our study, the CHA2DS2-VASc score of the patients with a flow < mTICI 2c after thrombectomy was found to be significantly higher than in the patients with a flow of mTICI 2c and 3 (4.1 ±1.5 vs. 3.04 ±1.6, p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this study, the CHA2DS2-VASc score was found to be significantly higher in the patient group with mTICI flow < 2c (2.78 ±1.44, 5.02 ±1.77, p < 0.001). In addition, a CHA2DS2-VASc score ≥ 3 was determined as a predictor of a failed attempt (area under the curve (AUC) = 0.827, 95% CI: 0.739–0.895, p < 0.001) [ 17 ]. Similarly, in our study, the CHA2DS2-VASc score of the patients with a flow < mTICI 2c after thrombectomy was found to be significantly higher than in the patients with a flow of mTICI 2c and 3 (4.1 ±1.5 vs. 3.04 ±1.6, p = 0.002).…”
Section: Discussionmentioning
confidence: 99%
“…Data on patient characteristics, laboratory data, risk of ischemic stroke (CHA 2 DS 2 -VASc score), and risk of hemorrhagic stroke (HAS-BLED score) were collected [ 11 ]. The CHA 2 DS 2 -VASc score was developed to predict thrombotic events in patients with AF and consists of congestive heart failure, hypertension, age ≥75 years, diabetes mellitus (DM), previous stroke, vascular disease, age of 65–74 years, and female sex [ 13 ]. The HAS-BLED score was developed to predict major bleeding events in anticoagulation for patients with AF and is composed of hypertension, abnormal renal or liver function, stroke, bleeding history or predisposition, labile PT-INR of anticoagulation, age >65 years, and concomitant use of drugs and alcohol [ 11 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Atorvastatin alleviates oxidative damage by activating the nuclear factor erythroid 2-related factor 2 pathway after brain ischemia in mice and anti-coagulation therapies, among others (3)(4)(5). However, these treatment methods have limited therapeutic efficacy, more contraindications, and bleeding risks, and as such, only few patients can benefit from them (6).…”
Section: Original Articlementioning
confidence: 99%